Unemployment, Economic Growth, and Government Expenditure in West Java: Perspectives from Dynamic Panel Model - Yahya Mahda Vikia; Farhan Hadi Prasetyo; Syifa Sa’adah (Jurnal Ekonomi Pembangunan, 2023)
The state plays a vital role in unemployment alleviation because the problem of unemployment can have serious economic, social, and political repercussions. West Java Province has had the highest unemployment rate in Indonesia in recent years. This study aims to determine and examine how the economic growth rate, government expenditure, labor force, and human development competence can affect the open unemployment rate in West Java Province in 2018-2022. The data used is panel data from 27 regencies/cities in West Java Province. The results showed that the economic growth rate has a negative relationship in the short and long term and directly validates the Okun Law in West Java. Government expenditure and HDI have a positive relationship to unemployment in the long run. The labor force has a negative relationship with unemployment in the short and long run. Thus, local governments need to address the availability of jobs through fiscal policy through effective and appropriate government expenditure. In addition, consider investment policies in works to overcome employment. However, when labor-intensive investment policies are implemented, it is essential to improve the skills of human resources through the Job Training Center (BLK).